Health professionals’ readiness for and factors influencing electronic medical record systems implementation in Southern Oromia, Ethiopia, 2024: a cross-sectional study - Gelchu, Miesa; Chala, Geleta; Tuke, Gemechis; Wodessa, Gelgelo; Ayele, Angefa; Yambo, Terefu; Fikrie, Anteneh (Frontiers in Digital Health, 2025)
BackgroundThe electronic medical record system is gradually being introduced in healthcare settings in high-income countries, but its adoption in low-resource settings like Ethiopia remains limited. There is a dearth of information regarding the readiness of health professionals to implement Electronic Medical Records system and the factors influencing this readiness, particularly in the study setting.ObjectiveThe study aimed to evaluate the readiness of healthcare professionals in Southern Oromia for the implementation of the electronic medical record system.MethodsA facility-based cross-sectional study was conducted using self-administered questionnaires among 384 health professionals from May 1–30, 2024, at public hospitals in the Borena and West Guji zones in southern Ethiopia. Epi Data version 4.6 and SPSS version 27.0 were used for data entry and analysis, respectively. The study used multivariable logistic regression to analyse factors influencing health professionals’ readiness to implement electronic medical record systems, assessing adjusted odds ratios with a 95% confidence interval and a p-value below 0.05, which is considered to declare statistical significance.ResultsHealth professionals, 60.4% [95% CI: (55.5–65.3%)] expressed readiness to utilize the Electronic Medical Record system. Factors associated with electronic medical record system readiness included younger age [AOR = 2.66, 95% CI: (1.06–6.67)], personal computer ownership [AOR = 3.54, 95% CI: (1.76–7.11)], adequate computer skills [AOR = 2.49, 95% CI: (1.41–4.39)], high computer literacy [AOR = 2.67, 95% CI: (1.53–4.66)], knowledge of electronic medical record system [AOR = 2.56, 95% CI: (1.53–4.29)], and a favorable attitude towards electronic medical record system [AOR = 2.77, 95% CI: (1.66–4.63)].ConclusionsThe study indicates that readiness for electronic medical record systems among health professionals is influenced by factors like younger age, computer ownership, skills, and positive attitudes. Interventions should target these factors, especially among older health professionals and those with limited digital literacy.